2021
DOI: 10.22141/2224-1507.2.22.2016.75759
|View full text |Cite
|
Sign up to set email alerts
|

Клініко-Патогенетична Значущість Остеоасоційованих Мікроелементів При Хворобах Суглобів. Повідомлення І. Мікроелементоз У Крові

Abstract: Резюме. Актуальность работы. Микроэлементоз (дисбаланс в организме уровней отдельных микроэлементов-МЭ) рассматривается как одно из важных клинико-патогенетических составляющих дегенеративно-воспалительных болезней суставов, а МЭ могут играть роль кофакторов, участвующих в процессах артикулярного воспаления. Цель работы: изучить уровни в сыворотке крови и провести оценку клинико-патогенетической значимости остеоассоциированных МЭ (кобальт-Со, медь-Cu, железо-Fe, литий-Li, марганец-Mn, свинец-Pb, стронций-Sr, ц… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Studying experimental osteoarthritis on mutant cell lines of chondrosarcoma SW1353 and model animals, it was found that increasing of zinc concentration in cell culture or adding it to the diet of rats reduces general oxidative stress, secretion of interleukin 1b, interleukin 13 and matrix metalloproteinase 13, thereby reducing the risk of osteoarthritis [26]. Studying the levels of microelementsin patients with rheumatic diseases, a decrease in zinc concentration was revealed only in osteoarthritis, magnesium concentration was reduced in osteoarthritis, rheumatoid arthritis, copper concentration was elevated in psoriatic arthritis [27]. According to the results of our research, a reduced concentration of zinc is associated with isolated JH.…”
Section: Discussionmentioning
confidence: 99%
“…Studying experimental osteoarthritis on mutant cell lines of chondrosarcoma SW1353 and model animals, it was found that increasing of zinc concentration in cell culture or adding it to the diet of rats reduces general oxidative stress, secretion of interleukin 1b, interleukin 13 and matrix metalloproteinase 13, thereby reducing the risk of osteoarthritis [26]. Studying the levels of microelementsin patients with rheumatic diseases, a decrease in zinc concentration was revealed only in osteoarthritis, magnesium concentration was reduced in osteoarthritis, rheumatoid arthritis, copper concentration was elevated in psoriatic arthritis [27]. According to the results of our research, a reduced concentration of zinc is associated with isolated JH.…”
Section: Discussionmentioning
confidence: 99%